Harold : the Last of the Saxon Kings $1 (BVolume 10s - Lytton, Edward Bulwer Lytton, Baron, 1803-1873 (Salt Lake City, UT : Project Gutenberg, 2005)
"Harold: the Last of the Saxon Kings $1 (BVolume 10" by Lytton is a historical novel likely written during the late 19th century. The narrative follows Harold, the Earl, as he grapples with the political turmoil and personal conflicts emerging in England during a crucial time in its history, focusing particularly on his interactions with significant characters like Bishop Alred and King Edward. The tale explores themes of loyalty, ambition, and the weight of oaths in a time of impending war and shifting allegiances. The opening of the book establishes a tense atmosphere as Harold returns to England amidst an unsettled political landscape, deeply troubled by the ramifications of an oath he feels bound to fulfill. He seeks absolution from Bishop Alred, who understands the nuances of Harold's predicament and ultimately supports his decision to prioritize the welfare of England over his oath to William. As Harold prepares for the pressures of leadership, the gathering storm of rebellion from the Northumbria$1 (Bled by Edwin and Morcar$1 (Bpoises him for a defining moment. The complexity of his relationships, particularly with family members like Tostig and his allies, sets the stage for a gripping saga of power struggles, loyalty, and the quest for justice amid the looming threat of Norman conquest. (This is an automatically generated summary.)s
Release date is 2005-03-01
This eBook was produced by Tapio Riikonen and David Widger
Keywords: Biographical fiction; Harold, King of England, 1022?-1066 -- Fiction; William I, King of England, 1027 or 8-1087 -- Fiction; Anglo-Saxons -- Kings and rulers -- Fiction; Great Britain -- History -- Edward, the Confessor, 1042-1066 -- Fiction; Great Britain -- Kings and rulers -- Fiction